Pluralismo constitucional interamericano: a leitura plural da constituição de 1988 e o diálogo entre o supremo tribunal federal e a corte interamericana de direitos humanos - MAGALHÃES, Breno Baía (Universidade Federal do Pará, 2017)
The thesis argues for the Constitutional Pluralism as a theory better suited to describe and explain the interactions between the 1988 Federal Constitution and the American Convention on Human Rights. Said interactions present themselves through the precedents of both the Supreme Court and the Inter-American Court of Human Rights. The thesis posits the theoretical fragility and the contextual mismatch of approaches based upon the monism/dualism dichotomy. Constitutional Pluralism, in turn, suggests the heterarchical interaction between constitutional orders through reciprocal influences. The supralegalty of international human rights treaties and the deference to regional constitutional interpretations enables the 1988 Constitution and the American Convention on Human Rights, respectively, to influence the substantive content of the fundamental and human rights through the deliberative dialogue between precedents and by having the construction of the pro homine principle as an ideal interpretive guide shared by both. Although Constitutional Pluralism is to be considered the theory that justifies the plural reading of the Brazilian constitutional provisions, the Supreme Court, despite the citations of the Inter-American Court of Human Rights precedents, does not dialogue with them.